Insights of healthcare providers and patients on implementation of dietary/lifestyle intervention for reversal of obesity and type 2 diabetes: a qualitative study - Lyngdoh, Tanica; Sharma, Neha; Zodpey, Sanjay (International Journal Of Community Medicine And Public Health, 2021)
Background: A diet plan that includes limiting eating frequency to twice a day along with other lifestyle modification was implemented as part of a campaign for diabetes reversal. The objective of this study was to identify facilitators and barriers to practice of this self-management regime among adults with type 2 diabetes mellitus (T2DM) living in urban communities. Methods: Participants included purposively sampled 10 diabetics recruited from 12 Diabetes Reversal Centres (DRCs) located across Maharashtra, Goa, Karnataka and Gujarat in India. Additionally, healthcare providers (including 10 doctors and 10 coordinators) from these centres were interviewed. Data collection employed in-depth interviews using structured interview guides. Thematic data analysis was undertaken to identify themes. Results: Continued rapport and supervisory role of the healthcare providers in the DRCs was the key facilitator in helping patients to assume responsibility and adhere to the diet regime for self-management. Visible reduction in sugar levels and body weight were other rewarding benefits that motivated sustained compliance. Social and cultural aspects (including social functions and formalities) was a perceived barrier that interfered with adherence to diet regime and goals. A common suggestion from both the healthcare providers and patients was the need to expand this initiative through capitalizing on use of relevant technological devices. Conclusions: In conclusion, a self-management patient model where there is continued and active involvement of healthcare providers through all stages is a recipe for success. However, this initiative can be further strengthened through complementing it with individualized, context-driven solutions to address the barriers.